O processo de inclusão digital no contexto de ensino e aprendizagem de língua inglesa na escola pública - Riciolli, Ana Maria Barbosa Varanda (2009)
This research focused on the process of digital inclusion within the context of English teaching and learning in two public schools in Uberlândia MG, in order to identify in which implementation stage these schools are in the present moment. We also aimed at analyzing how the process of digital inclusion was carried out in the context of English Language teaching in these schools, from the perspective of the director, the teacher and the student. Our study also investigated the policies and actions taken by the Administrators and participant schools, which intend to promote (and facilitate) the process of digital inclusion in the English Language setup. We noticed that, when it comes to English Language teaching, the public schools investigated have not effectively adopted the process of digital inclusion in pedagogical terms. This non-effectiveness seems to be the result of a tension between what the documents concerning the issue predict and what effectively happens in the schools in practical terms. This inclusion process is still facing different problems; ranging from practical, concrete issues regarding digitalization access, to those emerging from occasional negative convictions of people involved. Education managers, directors, teachers and students participated in our research. Data was gathered through interviews, questionnaires and classes observation. For the analysis of the corpus, we applied the method based on Carlo Ginsburg s Indiciary Paradigm (2007) and of the postulations proposed by Bax (2003), Chambers; Bax (2006), Sandholtz; Ringstaff; Dwyer (1997). It now seems possible that schools have already started their process of digital inclusion in their general practice. Regarding English Language however each school is in a different initial stage of digital inclusion.